Analisis Putusan Hakim Dalam Tindak Pidana Lingkungan Hidup Oleh Korporasi (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
This research aims to analyze the judge's decision regarding environmental crimes committed by corporations through Decision Number 190/Pid.B/LH/2020/PN Plw. This research uses a type of normative research with three approaches for the purposes of legal analysis and explanation, namely the case approach, statutory approach and conceptual approach. In contrast to previous research, this research specifically describes how judges interpret judges' interpretations in deciding cases of environmental crimes committed by corporations in more detail, not only from a criminal law perspective but also from the perspective of environmental law itself. The results of this research show that the Defendant in the